THE INFLUENCE OF CAPITAL STRUCTURE, CASH TURNOVER, LEVERAGE, LIQUIDITY, COMPANY ACTIVITIES, AND COMPANY SIZE ON PROFITABILITY IN MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Gunawan, Ripin; Susanto, Jonson; Pratiwi, Cyntia; Wulandari, Bayu; Habibie, Muhammad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of conducting this research is to find out how variables such as capital structure, cash turnover, liquidity, leverage, company size and company activities influence the level of profitability of manufacturing companies on the BEI. Statistics collected from 76 manufacturing companies on the IDX were used in this research, which was carried out using a quantitative approach. This test uses data from financial reports published by sample companies at www.idx.co.id. The research was applied using multiple linear regression. The findings from this study indicate that capital structure, cash turnover, LEVERAGE, LIQUIDITY, company activities, and company size influence the level of individual company profitability. Overall, all these elements influence the level of profitability of a manufacturing company. Keywords: Capital Structure, Cash Turnover, Leverage, Liquidity, Company Activities, Company Size and Profitability